Surface modification of aligned TiO2 nanotubes by Cu2O nanoparticles and their enhanced photo electrochemical properties and hydrogen generation application - Dubey P.K.; Kumar R.; Tiwari R.S.; Srivastava O.N.; Pandey A.C.; Singh P. (My University, 2025)
In this work, we report the synthesis of cuprous oxide (Cu2O) nanoparticles modified vertically oriented aligned titanium dioxide (TiO2) nanotube arrays through wet chemical treatment of TiO2 nanotubes and their multi-functional application as enhanced photo electrochemical and hydrogen generation. The synthesized samples were characterized by X-ray diffraction, SEM, TEM, and UV–Vis spectroscopy. The structural characterization revealed that the admixed Cu2O nanoparticles on the TiO2 surface did not alter its crystalline structure of vertically oriented aligned TiO2 nanotube. The photocatalytic performance and hydrogen generation of as synthesized Cu2O nanoparticles modified aligned TiO2 nanotube was found to highly depend on the Cu2O content. The optical characterizations reveal that the presence of Cu2O nanoparticles extends its absorption into the visible region which improves the photocurrent density in comparison to pristine aligned TiO2 nanotubes electrodes due to enhanced photoactivity and better charge separation. The optimum photocurrent density and hydrogen generation rate has been found to be 3.4 mA cm−2 and 127.5 μmole cm−2 h−1 in 1 M Na2SO4 electrolyte solution under 1.5 AM solar irradiance of white light with illumination intensity of 100 mW cm−2. © 2018 Hydrogen Energy Publications LLC